A global synthesis of the small‐island effect in amphibians and reptiles. Issue 1 (15th November 2021) - Gao, De; Wang, Yanping
Abstract : The small‐island effect (SIE) is an important pattern in the research fields of island biogeography and biodiversity science. Amphibians and reptiles, while playing important roles in ecosystems, are experiencing global declines. However, to date, no study has explicitly examined the generality and processes underlying the SIE in amphibians and reptiles. Here, we complied 105 global data sets to systematically evaluate the prevalence and underlying factors determining the occurrence of SIEs, area threshold ( T ) and difference in area threshold (Δ T ) between amphibians and reptiles. We applied 27 species–area relationship (SAR) models to the 105 global data sets of amphibians and reptiles to test for the existence of SIEs. We obtained 12 island characteristics, 5 environmental variables, 2 anthropogenic influence variables and 8 species traits that are linked to species survival, which were then tested separately and in combination to examine their roles in determining the occurrence of SIEs, area threshold and Δ T between amphibians and reptiles. We found SIEs in 20 out of 45 (44%) archipelagos for amphibians and 35 out of 60 (58%) archipelagos for reptiles. The occurrence of SIEs was affected by the number of islands, mean annual precipitation and minimum range size for amphibians, whereas only by the number of islands for reptiles. Area thresholds of amphibians were significantly higher than those of reptiles within the same true island system. Area thresholds were affected by mean island area and mean annual temperature for amphibians, whereas by mean island area, temperature seasonality and minimum range size for reptiles. Δ T was affected only by island type. Our study demonstrates that the determinants of the occurrence of SIEs and area thresholds comprised both extrinsic and intrinsic variables but differed substantially between amphibians and reptiles.